Participatory Design to Develop Montessori Modular Furniture for Pre-Prosperous Community Learning Center - Amanda Adelia Pranoto; Purnama Esa Dora Tedjokoesoemo; Poppy Fitratwentyna Nilasari; Sriti Mayang Sari (ITB Journal Publisher, LPPM ITB, 2021)
Education plays an important role in human development. Through learning, humans are enabled to write, speak, and create. The Covid-19 pandemic has disrupted education, especially for those who depend on free educational programs that rely on volunteers for day-to-day operation. Children in the golden age are the most affected. Online learning can never cover the social interaction provided by offline learning. This research was done in Rumah Langit, which is a free community learning center for children, located in Rusunawa Urip Sumoharjo, Surabaya. After several months of getting to know the people involved, their surrounding environment, and participating in their daily activities, it could be clearly seen that Rumah Langit was lacking learning media. Especially learning media for children in the golden age who are often very curious and are in the stage of developing their five senses. OTTM (One, Two, Three, More?) is a modular furniture unit specifically developed for learning media at home for preschoolers, designed using the six steps of the design thinking method (Understand, Observe, Define Point of View, Ideate, Prototype, and Test). With its endless configurations, OTTM can be used as an open storage, a table and chair set for preschoolers, a seating chair for adults, and learning media for kids. It was inspired by the Montessori method of learning, which allows children to be creative and learn at their own pace. OTTM offers an easy and fun way of learning at home for children, especially for children in the golden age. By using OTTM, children can learn about basic counting, colors and how primary colors create secondary colors, and about shapes, from geometric to organic shapes.